Implementation and preliminary clinical application of a robotic thoracic telesurgery program in a middle-income country: a structured pathway from simulation to clinical practice - Ricardo Mingarini Terra; Pedro Henrique Xavier Nabuco de Araujo; Marcos Naoyuki Samano; Fabio Eiti Nishibe Minamoto; Everson Luiz Almeida Artifon; Jose Pinhata Otoch; Paulo Manuel Pego-Fernandes (Journal of Robotic Surgery, 2026)
Abstract Telesurgery may help overcome geographic disparities in access to specialized surgical care. Although recent studies confirm the technical feasibility of robotic thoracic telesurgery, most reports originate from highly controlled settings, and practical implementation within public healthcare systems remains scarce. We describe the development and preliminary clinical application of a robotic thoracic telesurgery program in a middle-income country, reported as a proof-of-implementation case series rather than a statistically validated model. A robotic thoracic telesurgery program was developed connecting the University of São Paulo Medical School (FMUSP) and University Hospital (HU-USP), approximately 10 km apart, using the Toumai® platform over the institutional fiber-optic network. Development included infrastructure deployment, preclinical network validation (28 robotic surgeons), safety-protocol development, and team training, culminating in two remotely performed procedures under a pre-defined, manufacturer-limited case allocation. A robotic wedge resection for pulmonary metastasis and a robotic left upper trisegmentectomy with systematic lymphadenectomy were completed entirely under remote control, with the surgeon at FMUSP and the patient at HU-USP. Neither procedure had communication interruptions, packet loss, conversion events, or intraoperative complications; maximum latency did not exceed 12 milliseconds. Chest tubes were removed on postoperative day 1 in both patients, with discharge on day 1 and 2, respectively. This early experience supports the technical feasibility of introducing robotic thoracic telesurgery within a public healthcare system through a structured implementation pathway. Given the small sample, conclusions remain preliminary; the model’s value lies not in extending distance, but in outlining a reproducible process for expanding access to specialized surgical expertise.